Trait impulsivity in Juvenile Myoclonic Epilepsy. Issue 1 (2nd December 2020) - Shakeshaft, Amy; Panjwani, Naim; McDowall, Robert; Crudgington, Holly; Peña Ceballos, Javier; Andrade, Danielle M.; Beier, Christoph P.; Fong, Choong Yi; Gesche, Joanna; Greenberg, David A.; Hamandi, Khalid; Koht, Jeanette; et al.
Abstract: Objective: Impulsivity is a multidimensional construct that can predispose to psychopathology. Meta‐analysis demonstrates an association between response impulsivity and Juvenile Myoclonic Epilepsy (JME), a common genetic generalized epilepsy. Here, we test the hypotheses that trait impulsivity is (i) elevated in JME compared to controls; (ii) moderated by specific seizure characteristics; and (iii) associated with psychiatric adverse effects of antiepileptic drugs (AEDs). Methods: 322 participants with JME and 126 age and gender‐matched controls completed the Barratt's Impulsiveness Scale (BIS‐brief) alongside information on seizure history and AED use. We compared group BIS‐brief scores and assessed associations of JME BIS‐brief scores with seizure characteristics and AED adverse effects. Results: The mean BIS‐brief score in JME was 18.1 ± 4.4 compared with 16.2 ± 4.1 in controls ( P  = 0.0007). Elevated impulsivity was associated with male gender ( P  = 0.027), frequent absence seizures ( P  = 0.0004) and lack of morning predominance of myoclonus ( P  = 0.008). High impulsivity significantly increased the odds of a psychiatric adverse event on levetiracetam ( P  = 0.036), but not any other psychiatric or somatic adverse effects. Interpretation: Trait impulsivity is elevated in JME and comparable to scores in personality and neurotic disorders. Increased seizure frequency and absence of circadian seizure pattern moderate BIS score, suggesting disruption of both cortico‐striatal and thalamocortical networks as a shared mechanism between seizures and impulsivity in JME. These findings warrant consideration of impulsivity as a distinct target of intervention, and as a stratifying factor for AED treatment in JME, and perhaps other types of epilepsy. The role of impulsivity in treatment adherence and psychosocial outcome requires further investigation.